2018
DOI: 10.1111/faf.12264
|View full text |Cite
|
Sign up to set email alerts
|

Otolith chemistry does not just reflect environmental conditions: A meta‐analytic evaluation

Abstract: Fish otoliths are widely used to answer biological and ecological questions related to movements and habitat use based on their chemical composition. Two fundamental assumptions underlie otoliths as environmental tracers and proxies for reconstructing exposure histories: (i) otolith chemistry reflects water chemistry, and (ii) ambient environmental conditions affect otolith element incorporation. Here, we test these assumptions for Sr and Ba through meta‐analyses. Our first meta‐analysis confirmed a correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 90 publications
3
69
1
1
Order By: Relevance
“…A number of studies have reported the correlation between environmental exposure and otolith chemistry for Ba and Sr (Elsdon & Gillanders, 2004;Izzo, Reis-Santos, & Gillanders, 2018;Martin et al, 2013;Walther & Thorrold, 2006). The values of slope of the linear regressions estimated for Ba:Ca and Sr:Ca ratios (0.026 and 0.211 respectively in the present study) were nearly comparable to the earlier reported studies for a number of fish species such as…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies have reported the correlation between environmental exposure and otolith chemistry for Ba and Sr (Elsdon & Gillanders, 2004;Izzo, Reis-Santos, & Gillanders, 2018;Martin et al, 2013;Walther & Thorrold, 2006). The values of slope of the linear regressions estimated for Ba:Ca and Sr:Ca ratios (0.026 and 0.211 respectively in the present study) were nearly comparable to the earlier reported studies for a number of fish species such as…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, while intrinsic factors influence element incorporation into otoliths (Izzo et al. ), low DO (1.7 mg/L) alone did not result in elevated otolith Mn in Atlantic Croakers, suggesting extrinsic (i.e., sediment‐derived) Mn origins (Mohan et al. ).…”
mentioning
confidence: 99%
“…Fish from Clarence River may have had a higher proportion of crustaceans in their diet (due to their small size) than the fish from some of the other estuaries (Schilling et al 2017), and this may have been reflected by the high Ba:Ca ratios found for this group. However, this pattern was not seen in similarly small fish collected from Jervis Bay, suggesting, conversely, that diet had a limited impact on Ba:Ca ratios in this group (Izzo et al 2018). N evertheless, these patterns could simply reflect the higher freshwater input in Clarence River compared with in Jervis Bay.…”
Section: Juvenile Otolith Chemistry Differencesmentioning
confidence: 77%
“…temperature, salinity) factors in addition to a simple relationship with water chemistry (Sturrock et al 2014, Grammer et al 2017. A recent meta-analysis highlighted this by demonstrating that whilst salinity was the primary driver of both Ba and Sr, Sr was also influenced by factors including the ecological niche, condition, diet and ontogeny of individual species (Izzo et al 2018). As such, it is important to note that factors such as diet may be influencing the Sr:Ca profiles presented here (Engstedt et al 2012).…”
Section: Elemental Profilesmentioning
confidence: 99%